If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x(x+7)=(6x+42)
We move all terms to the left:
6x(x+7)-((6x+42))=0
We multiply parentheses
6x^2+42x-((6x+42))=0
We calculate terms in parentheses: -((6x+42)), so:We get rid of parentheses
(6x+42)
We get rid of parentheses
6x+42
Back to the equation:
-(6x+42)
6x^2+42x-6x-42=0
We add all the numbers together, and all the variables
6x^2+36x-42=0
a = 6; b = 36; c = -42;
Δ = b2-4ac
Δ = 362-4·6·(-42)
Δ = 2304
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{2304}=48$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(36)-48}{2*6}=\frac{-84}{12} =-7 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(36)+48}{2*6}=\frac{12}{12} =1 $
| X^3-5x^2-7x-2=0 | | x^2+x-2.304=0 | | (3x+20)/6=14 | | 12z-7-11z=5-5 | | 2x-11=23 | | 1x-10=100 | | 9x-85=60 | | 9x-45=60 | | 5(m-3)=3 | | 5x+4×4=7x+4×3 | | 3x2/2=320 | | 4/3x+3/2+1=125/18 | | r-11/6=-41/30+10/3r | | 12x÷5=x-5 | | 4/3x+3/2+1=125/8 | | 8x-46=40 | | 16-2.4s=-8 | | 1x-10=0 | | 9x-45=80 | | 2(y+3)-3y=8-2(2y-5) | | 45-95=5x | | 9-99=3x | | 5-105=5x | | X^2+71x-3162=0 | | 24=8m/5 | | X^2+10x-527=0 | | n-28=12 | | x+4x-4=9 | | 1/3(2x-1)-(2x+1)=1/12(2-x) | | 2-2x=8+x | | I+6+4r=126 | | 3/2+t=3/2 |